Mycotoxins: Emerging toxic mechanisms, and unanswered research questions - Wu, Qinghua; You, Li; Wu, Wenda; Long, Miao; Kuca, Kamil (Food and chemical toxicology, 2023)
Recently, a series of toxic mechanisms have been explored in mycotoxins. Emerging evidence show that mycotoxins may induce human neurodegenerative diseases (ND); however, this idea is still unproven. Besides to identify this hypothesis, some questions, for example, how the mycotoxins induce this disease and what the molecular mechanism is, as well as whether the brain-gut axis is involved in this context, should be answered. Very recent studies further reported an “immune evasion” mechanism in trichothecenes; moreover, hypoxia seems to play important function in this process; nevertheless, whether this “immune evasion” process is present in other mycotoxins, especially in aflatoxins, should be tested. In this work, we mainly discussed some key scientific questions that need to be answered in the toxic mechanisms of mycotoxins. We especially focused on the research questions in the key signaling pathways, balance mechanism of immunostimulatory and immunosuppressive effects, and the relationship between autophagy and apoptosis. Interesting topics such as mycotoxins and aging, cytoskeleton and immunotoxicity are also discussed. More importantly, we compile a special issue: “New insight into mycotoxins and bacterial toxins: toxicity assessment, molecular mechanism and food safety” for Food and Chemical Toxicology. Researchers are encouraged to submit their newest work to this special issue.